Catalytic Conversion of 5-Hydroxymethylfurfural and Fructose to 5-Ethoxymethylfurfural over Sulfonated Biochar Catalysts - Ziting Du; Fukun Li; Ronghe Yang; Qingya Cao; Delong Yang; Jinhang Dai (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
5-Hydroxymethylfurfural (HMF) is a key platform compound that can be produced by the dehydration of typical carbohydrates like glucose and fructose. Among the derivatives of HMF, 5-ethoxymethylfurfural (EMF) is the etherification product of HMF with ethanol. Owing to some advantages (i.e., high energy density), EMF has been regarded as a potential liquid fuel. Therefore, catalytic conversion of HMF and fructose to EMF is of significance, especially using heterogeneous catalysts. In this paper, we demonstrated the preparation of biomass-based catalysts for the synthesis of EMF from HMF and fructose. Some sulfonated biochar catalysts were prepared by the carbonization of biomass-based precursors at high temperature in N2, followed by the subsequent sulfonation process employing concentered H2SO4 as sulfonation reagent. The obtained catalysts were characterized by scanning electron microscope (SEM), Fourier transform infrared spectrometer (FT-IR), X-ray diffraction (XRD), and element analysis. The catalytic conversion of HMF to EMF was carried out in ethanol, providing a 78% yield with complete conversion at 120 °C. The catalytic activity of the used catalyst showed slight decrease for the etherification of HMF. Moreover, the catalysts were effective for the direct conversion of fructose towards EMF in 64.9% yield. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).